Messenger RNA Coronavirus Disease 2019 (COVID-19) Vaccination With BNT162b2 Increased Risk of Bell's Palsy: A Nested Case-Control and Self-Controlled Case Series Study. (7th June 2022) - Wan, Eric Yuk Fai; Chui, Celine Sze Ling; Ng, Vanessa Wai Sei; Wang, Yuan; Yan, Vincent Ka Chun; Lam, Ivan Chun Hang; Fan, Min; Lai, Francisco Tsz Tsun; Chan, Esther Wai Yin; Li, Xue; Wong, Carlos King Ho; Chung, Raccoon Ka Cheong; et al.
Abstract: Background: Observable symptoms of Bell's palsy following vaccinations arouse concern over the safety profiles of novel coronavirus disease 2019 (COVID-19) vaccines. However, there are only inconclusive findings on Bell's palsy following messenger (mRNA) COVID-19 vaccination. This study aims to update the previous analyses on the risk of Bell's palsy following mRNA (BNT162b2) COVID-19 vaccination. Methods: This study included cases aged ≥16 years with a new diagnosis of Bell's palsy within 28 days after BNT162b2 vaccinations from the population-based electronic health records in Hong Kong. Nested case-control and self-controlled case series (SCCS) analyses were used, where the association between Bell's palsy and BNT162b2 was evaluated using conditional logistic and Poisson regression, respectively. Results: Totally 54 individuals were newly diagnosed with Bell's palsy after BNT162b2 vaccinations. The incidence of Bell's palsy was 1.58 (95% confidence interval [CI], 1.19–2.07) per 100 000 doses administered. The nested case-control analysis showed significant association between BNT162b2 vaccinations and Bell's palsy (adjusted odds ratio [aOR], 1.543; 95% CI, 1.123–2.121), with up to 1.112 excess events per 100 000 people who received 2 doses of BNT162b2. An increased risk of Bell's palsy was observed during the first 14 days after the second dose of BNT162b2 in both nested case-control (aOR, 2.325; 95% CI, 1.414–3.821) and SCCS analysis (adjusted incidence rate ratio, 2.44; 95% CI, 1.32–4.50). Conclusions: There was an overall increased risk of Bell's palsy following BNT162b2 vaccination, particularly within the first 14 days after the second dose, but the absolute risk was very low. Abstract : There was an overall increased risk of Bell's palsy following BNT162b2 vaccination, particularly within the first 14 days after the second dose, but absolute risk was low. The benefits from coronavirus disease 2019 vaccination still outweigh the small risk of Bell's palsy.